The Financial Effect(s) and Analysis of Coach-Athlete Educational Relationship: A Case Study of Youth Soccer Players in San Diego and Orange County. - Ejiro Uriri Osiobe; Daniel O. Jones; Davi Sofyan; Nate Houser (Indonesian Journal of Sport Management, 2023)
The coach-athlete relationship and its educational effectiveness are ambiguous, with several perceptions of creating an engaging learning environment. Thus, understanding this relationship and analyzing its impact is essential to increasing enrollment and retention rates within institutions that associate with youth athletes. The study reviews existing literature on coach effectiveness and youth-athlete relationship and analyses primary datasets from elite academy soccer clubs in the San Diego and Orange County area. The results provide valuable information on athletes' and parents' decision(s) on what club they want to join based on the coach-athlete educational relationship and behaviors using a qualitative analysis approach.